Phytochemical assessments of Astragalus hamosus pods (Iklil-ul-Malik) - Azadeh Hamedi; Mohammad M. Zarshenas; Maryam Sohrabpour (Shiraz University of Medical Sciences, 2016)
Authentication and quality control of herbs in herbal markets is an important challenge for practitioners and food and drug organizations. Rapid and simple pharmacognostic evaluations are beneficial to overcome this problem. On the other hand, there is a mist about the scientific names of some of these herbs even in scientific literatures. Iklil-ul-Malik or Astragalus hamosus L. (Papilionaceae) is one of these medicinal plants.Pharmacognostic (macroscopic, microscopic and phytochemical) properties of Iklil-ul-Malik pods were investigated. Different ash and extractive values were determined. The HPTLC finger prints of the herbs' fractions were prepared, using different reagents and mobile phases. The fatty acids, steroids, alkene and terpenoids of the pods were investigated by GC-MS analysis. Soluble fatty acid and soluble sugar content were determined by spectroscopic methods. Total ash, acid insoluble and water soluble ash were determined to be 75.00±11.83, 8.33±2.89 and 40.00±5.00 mg/g respectively. The extractive values for n-hexane, dichloromethane and ethanol fractions were 0.77%, 0.16% and 0.49% (w/w). Free amino acid and soluble sugar contents were respectively 3.33±0.001 and 8.83±0.004 (w/w %). Polyphenols, triterpenes, glycosides and glycolipids were detected in different fractions. The principal fatty acids were linoleic acid (48.64%), linolenic acids (25.35%), lauric acid (8.12%) and stearic acid (6.38%). By presenting the pharmacognostic values and HPTLC fingerprints in this manuscript, the herb can be authenticated.